Avian Diversity and Feeding Guilds in a Secondary Forest, an Oil Palm Plantation and a Paddy Field in Riparian Areas of the Kerian River Basin, Perak, Malaysia - Nur Munira Azman; Nurul Salmi Abdul Latip; Shahrul Anuar Mohd Sah; Mohd Abdul Muin Md Akil; Nur Juliani Shafie; Nurul Liyana Khairuddin (Tropical Life Sciences Research, 2011)
The diversity and the feeding guilds of birds in three different habitats (secondary forest, oil palm plantation and paddy field) were investigated in riparian areas of the Kerian River Basin (KRB), Perak, Malaysia. Point-count observation and mistnetting methods were used to determine bird diversity and abundance. A total of 132 species of birds from 46 families were recorded in the 3 habitats. Species diversity, measured by Shannon’s diversity index, was 3.561, 3.183 and 1.042 in the secondary forest, the paddy field and the oil palm plantation, respectively. The vegetation diversity and the habitat structure were important determinants of the number of bird species occurring in an area. The relative abundance of the insectivore, insectivore-frugivore and frugivore guilds was greater in the forest than in the monoculture plantation. In contrast, the relative abundance of the carnivore, granivore and omnivore guilds was higher in the plantation. The results of the study show that the conversion of forest to either oil palm plantation or paddy fields produced a decline in bird diversity and changes in the distribution of bird feeding guilds. Kajian kepelbagaian dan kumpulan pemakanan burung di tiga habitat berbeza (hutan sekunder, kelapa sawit dan sawah padi) telah dijalankan di kawasan riparian Lembangan Sungai Kerian, Perak, Malaysia. Tinjauan melalui kaedah point-count dan pemasangan jaring kabut (mist-netting) telah digunakan untuk menentukan kepelbagaian burung dan kelimpahannya. Sebanyak 132 spesies burung daripada 46 famili telah direkodkan di 3 habitat tersebut. Kepelbagaian spesies diukur melalui indeks kepelbagaian Shannon’s dengan catatan masing-masing sebanyak 3.561, 3.183 dan 1.042 di hutan sekunder, sawah padi dan kelapa sawit. Kepelbagaian tumbuhan dan struktur habitat merupakan penentu utama kehadiran bilangan spesies burung di sesuatu kawasan. Kelimpahan relatif kumpulan pemakanan insektivor, insektivor-frugivor dan frugivor adalah lebih banyak di kawasan hutan berbanding di kawasan penanaman monokultur. Sebaliknya, kelimpahan relatif kumpulan pemakanan karnivor, grainivor dan omnivor adalah tinggi di kawasan penanaman. Hasil kajian menunjukkan, perubahan kawasan hutan kepada kawasan kelapa sawit atau sawah padi menghasilkan penurunan spesies burung dan perubahan taburan kumpulan pemakanan burung.